The establishement of moral level predictors for construction project managers in China - Xue, Fei, 1989-, author 599670; Tareef Hayat Khan, supervisor 604967; Fakulti Alam Bina 8041 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2016